ANALISIS KUALITAS, KUATITAS DAN KINERJA (K3) PEGAWAI PADA BADAN PUSAT STATISTIK KABUPATEN KERINCI: M.Dhany Alsunah - Alsunah, M. Dhany (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2020)
Thesis. Analysis of Quality, Quantity and Performance (K3) of Employees at the Central Statistics Agency of Kerinci Regency. The Central Bureau of Statistics is an organization that has been established based on Presidential Regulation Number 86 of 2007 concerning the Central Statistics Agency and the Regulation of the Head of the Central Statistics Agency Number 7 of 2008 concerning the Organization and Work Procedure of The Central Statistics Agency located in Kerinci Regency. The formulation of the research problem, namely, what is the Quality, Quantity and Performance (K3) of Employees at the Central Statistics Agency of Kerinci Regency? The research objective is to see the quality, quantity and performance (K3) of the employees of the Central Statistics Agency of Kerinci Regency. This research uses a qualitative approach where data is obtained through field interview guides to 7 informants who refer to the research indicators, namely 1. Knowledge. 2. Skills. 3. Capability 4. Number of Hours Worked. 5. Use of time. 6. Responsibility. 7. Quantity of work. 8. Work quantity. 9. Punctuality of time. 10. Work effectiveness. 11. Independence. 12. Work Commitment. The data obtained in the field were analyzed based on the classification of the informants’ answers which were described in the results and discussion of the research which was then carried out by the interpreter of the researcher. It is known that the Quality, Quantity and Performance (K3) of employees at the Central Bureau of Statistics of Kerinci Regency have been carried out properly according to its rules and main duties, only one research indicator that has not been implemented is the indicator of independence. Where employees are not all independent in carrying out tasks such as new employees and employees who occupy a room or work with new job duties. For this reason, the authors suggest that employees at the Central Statistics Agency of Kerinci Regency can maintain and continue to strive to continue to do innovation and creativity in work and increase employee Independence.